Prevalence and prognostic significance of device-detected subclinical atrial fibrillation in patients with heart failure and reduced ejection fraction. (1st August 2020) - Zakeri, Rosita; Morgan, John M.; Phillips, Patrick; Kitt, Sue; Ng, G. Andre; McComb, Janet M.; Williams, Simon; Wright, David J.; Gill, Jaswinder S.; Seed, Alison; Witte, Klaus K.; Cowie, Martin R.; et al.
Abstract: Background: Cardiac implanted electronic devices (CIEDs) can detect short durations of previously unrecognised atrial fibrillation (AF). The prognostic significance of device-detected subclinical AF, in the context of contemporary heart failure (HF) therapy, is unclear. Methods: Amongst patients enrolled in the Remote Monitoring in HF with implanted devices (REM-HF) trial, three categories were defined based on total AF duration in the first year of follow-up: no AF, subclinical AF (≥6 min to ≤24 h), and AF >24 h. All-cause mortality, stroke, and cardiovascular hospitalisation were assessed. Results: 1561 patients (94.6%) had rhythm data: 71 (4.6%) had subclinical AF (median of 4 episodes, total duration 3.1 h) and 279 (17.9%) had AF >24 h. During 2.8 ± 0.8 years' follow-up, 39 (2.5%) patients had a stroke. Stroke rate was highest amongst patients with subclinical AF (2.0 per 100-person years) versus no AF or AF >24 h (0.8 and 1.0 per 100-person years, respectively). In the overall cohort, AF >24 h was not an independent predictor of stroke. However, amongst patients with no history of AF (n = 932), new-onset subclinical AF conferred a three-fold higher stroke risk (adjusted HR 3.35, 95%CI 1.15–9.77, p = 0.027). AF >24 h was associated with more frequent emergency cardiovascular hospitalisation (adjusted HR 1.46, 95%CI 1.19–1.79, p < 0.0005). Neither AF classification was associated with mortality. Conclusions: In patients with HF and a CIED, subclinical AF was infrequent but, as a new finding, was associated with an increased risk of stroke. Anticoagulation remains an important consideration in this population, particularly when the clinical profile indicates a high stroke risk. Highlights: Subclinical AF occurred in <5% of patients with HF and an implanted device. New-onset subclinical AF was associated with a three-fold increased risk of stroke. AF longer than 24-hours' total duration increased CV hospitalisation risk. AF did not increase the risk of mortality in the context of contemporary HF therapy.